Entre Zola e Eça: o Naturalismo brasileiro em seu apogeu (1888) - Simões Júnior, Alvaro Santos [UNESP] (My University, 2012)
Brazilian naturalism began in 1881 with the publication of O mulato by Aluísio Azevedo. In spite of the considerable Brazilian cultural dependence on France, the great European master of Brazilian naturalists was initially the Portuguese Eça de Queirós. His novel O primo Basílio resounded intensely in the intellectual environment of Rio de Janeiro, where it had found admirers and fierce critics like Machado de Assis. Only around 1888, when the French naturalist movement suffered serious defections, Brazilian novelists adopted Émile Zola’s esthetical proposals directly through the reading of the Rougon-Macquart cycle. In that year, O missionário by Inglês de Sousa, O cromo by Horácio de Carvalho, A carne by Júlio Ribeiro, Hortência by Marques de Carvalho, Uma família baiana by Xavier Marques, and Lar by Pardal Mallet were published. Nevertheless, it is relevant to consider which features of Zola’s and Eça’s works were incorporated in those works which established a flowering moment of Brazilian naturalism.

O naturalismo brasileiro começou em 1881 com a publicação do romance O mulato, de Aluísio Azevedo. Apesar da grande dependência cultural do Brasil diante da França, o grande mestre europeu dos naturalistas brasileiros foi inicialmente o português Eça de Queirós. Seu romance O primo Basílio (1878) repercutiu intensamente no meio intelectual do Rio de Janeiro, onde encontrou admiradores entusiastas e também críticos impiedosos como Machado de Assis. Apenas por volta de 1888, quando o naturalismo francês sofria sérias defecções, alguns romancistas brasileiros adotaram as propostas estéticas de Émile Zola diretamente através da leitura do ciclo dos Rougon-Macquart. Naquele ano, publicaram-se vários romances: O missionário, de Inglês de Sousa, O cromo, de Horácio de Carvalho, A carne, de Júlio Ribeiro, Hortência, de Marques de Carvalho, Uma família baiana, de Xavier Marques, e Lar, de Pardal Mallet. Torna-se relevante considerar quais características das obras de Zola e Eça foram incorporadas aos romances publicados em 1888, ano que representa o ápice do naturalismo brasileiro.
Between Zola and Eça: brazilian naturalism at its zenith (1888)
Keywords: Brazilian naturalism; Cultural dependence; Eça de Queirós; Émile Zola; European naturalism; Novel; Dependência Cultural; Eça de Queirós; Émile Zola; Naturalismo brasileiro; Naturalismo europeu; Romance